Alcohol and drug problems and sexual and physical abuse at three urban high schools in Mthatha - O.A. Betancourt; M.M. Herrera (South African Family Practice)
Background: Alcohol is the most important substance of abuse in South Africa. There are, however, reports of an increase in the use of other drugs among adolescents. The aim of this study was to assess the use of alcohol and other drugs of abuse and their association with physical or sexual abuse in three urban high schools in Mthatha.